Evolução morfodinâmica da região de influência estuarina do Rio Curimataú/RN, com ênfase nas alternativas do ambiente deposicional de manguezal e a integração de geodados em Sig - Souza, Flavo Elano Soares de (2004)
The estuaries are important investigation zones of the actual morphodynamic and of depositional facies of recent geological history. They are constituted in important receptor means of the coastal area sediments, where the evolutionary processes occur quickly. They are also attractive means for the development of anthropic activities, which in a disordered way interfere in the active processes in the sedimentary balance of the coastal areas. Among the human interventions, the alterations of the depositional environment of mangroves in areas of tropical estuary is deserving relevance, whose implications for the environment estuarine and the coastal adjacent, they are still far to be known. Due to the interest of the sedimentologic component in the comprehension of the processes linked to the evolution of the environments estuarine and coastal adjacent, this work, aimed at the understanding of the morphodynamic coastal phenomena that comprise the region of estuarine influence of the River Curimataú / RN. It was also evaluated in the morphodynamic context the implications due to alterations of the depositional environment of mangrove by anthropic activity. The Curimataú Estuary, located in the south portion of the oriental coast of Rio Grande do Norte, in the last decades has been objective of the overwhelming occupation of the shrimp farm in areas of mangroves, which were implanted with perspectives of development in a short to medium period. On the other hand, the estuary and its region of coastal influence lacks enough information to subsidize the planning and reorganization more effective of the surrounding activities. Thus, it was intended with this work to give a contribution target tothe maintainable use of the coastal resources of this region. A series of studies using data of orbital and acoustic remote sensing, as of sediments sampling, were executed in the gutter of the estuary. The obtained results starting from the interpretation of bathymetric maps, echo sounder graphics and of distribution of sediments made possible the location of the estuary based in morpho-sedimentar criteria. The estuarine tidal flat was dissected in environments of intertidal mangroves, supratidal mangroves and apicuns with base in the integration of data of sensor optic and of radar following by the field control. The adjacent coast that is influenced by the Curimataú estuary, was segmented according to their geomorphologic characteristics, where each segment had a point of observation of the beach morphodynamic, during the period from january/2001 to february/2002. Once every month, beaches profiles, collections of sediments in the beach zones, as measurement of hydrodynamic parameters were executed. The results of the observations of the tidal environment showed that the area of estuarine influence of the Curimataú begins to suffer negative sedimentary taxes, where in some beaches, the erosive processes are already observed. The granulometric characteristics of the beach sediments start to tend for the increase of thin sand in the erosive periods. The destruction of the depositional environments of mangroves of the Curimataú estuary, to the construction of shrimp farms, can be providing the diminution of the tidal prism of the estuary, enlarging the effects of the local increasing of the sea level, through the smaller supplying of sediments to the adjacent coast. Besides this, it was verified the possibility of the sanding of the tidal channel in the margins of the destroyed areas of mangroves, where very high taxes of sedimentation of thin materials were estimated in case of these areas were preserve